Relationships between personality, gender role, social support and severity of wife abuse among women in Tehran, Iran - Motevaliyan, Seyed Mehdi (2013)
Wife abuse has negative consequences on wife, family and society. Wife abuse is influenced by various factors. The present study was conducted to determine the relationships between personality, social support, gender role attitude, and severity of wife abuse among Iranian women in Tehran. The study involved 398 women who sought treatment in 4 selected hospitals in Tehran City. The respondents were identified by using multistage stratified sampling technique. This study is a cross sectional study, and the required data were collected by using structured questionnaire. Conflict Tactic Scale (CTS2) was used to measure severity of wife abuse. Five-Factor Personality Inventory (NEO-FFI) measured personality, while Multidimensional Scale of Perceived Social Support (MSPSS) was used to measure social support. Gender role attitude was measured using Sex Role Attitudinal Inventory (SRAI). Descriptive statistics, Spearman correlation coefficients, Kruskal-Wallis Test and nonparametric Mann-Whitney U Test were used to describe data at univariate and bivariate levels. Multinomial logistic regression was used to determine predictors of the severity of wife abuse. Findings showed that only 14% of the respondents never been abused by husband during last year. A total of 42.5% received minor abuse and 43.5% received severe abuse. Significant positive relationships were established between severity of total abuse, psychological abuse, physical abuse, injury and sexual abuse with neuroticism personality. Furthermore, significant negative relationships between severity of total abuse, sexual abuse, injury, and psychological abuse with extroversion personality were also established. However, no significant relationship existed between openness personality and wife abuse. Agreeableness and conscientiousness personalities had significant negative relationships with severity of total wife abuse, psychological abuse, injury, physical abuse and sexual abuse. Level of social support had significant negative relationship with severity of total wife abuse. The result of the study also showed a significant positive relationship between feminist gender role attitude and severity of wife abuse. Multinomial logistic regression results indicated that neuroticism personality trait was a significant predictor of minor and severe total abuse, psychological abuse, severe physical abuse, and injury. Experience of father insult was a significant predictor of severe total abuse. Moreover, experience of witnessing mother punished by father was a significant predictor of severe psychological and physical abuse and injury. The results of the current study highlighted the importance of personality traits, social support and gender role attitude in explaining the severity of wife abuse in Tehran, Iran. Therefore, strategies to prevent and intervene causes of abuse among wives in Tehran, Iran should focus on their personality, support system available for them, and also their attitude related to gender role.